Ecology of active rock glaciers and surrounding landforms: climate, soil, plants and arthropods. (2nd January 2017) - Tampucci, Duccio; Gobbi, Mauro; Marano, Giuseppe; Boracchi, Patrizia; Boffa, Giacomo; Ballarin, Francesco; Pantini, Paolo; Seppi, Roberto; Compostella, Chiara; Caccianiga, Marco
Abstract : Active rock glaciers are periglacial landforms consisting of coarse debris with interstitial ice or ice‐core. Recent studies showed that such landforms are able to support plant and arthropod life and could act as warm‐stage refugia for cold‐adapted species due to their microclimate features and thermal inertia. However, integrated research comparing active rock glaciers with surrounding landforms to outline their ecological peculiarities is still scarce. We analysed the abiotic (ground surface temperature and humidity, soil physical and chemical parameters) and biotic (plant and arthropod communities) features of two Alpine active rock glaciers with contrasting lithology (silicate and carbonate), and compared them with the surrounding iceless landforms as reference sites (stable slopes and active scree slopes). Our data show remarkable differences between stable slopes and unstable landforms as a whole, while few differences occur between active scree slopes and active rock glaciers: such landforms show similar soil features but different ground surface temperatures (lower on active rock glaciers) and different occurrence of cold‐adapted species (more frequent/abundant on active rock glaciers). Both plant and arthropod species distributions depend mainly on the geographical context as a function of soil pH and on the contrast between stable slopes and unstable landforms as a function of the coarse debris fraction and organic matter content, while the few differences between active scree slopes and active rock glaciers can probably be attributed to microclimate. The role of active rock glaciers as potential warm‐stage refugia for cold‐adapted species is supported by our data; however, at least in the European Alps, their role in this may be less important than that of debris‐covered glaciers, which are able to host cold‐adapted species even below the climatic tree line.